2011
DOI: 10.1016/j.bcp.2011.05.008
|View full text |Cite
|
Sign up to set email alerts
|

The four cysteine residues in the second extracellular loop of the human adenosine A2B receptor: Role in ligand binding and receptor function

Abstract: The adenosine A(2B) receptor is of considerable interest as a new drug target for the treatment of asthma, inflammatory diseases, pain, and cancer. In the present study we investigated the role of the cysteine residues in the extracellular loop 2 (ECL2) of the receptor, which is particularly cysteine-rich, by a combination of mutagenesis, molecular modeling, chemical and pharmacological experiments. Pretreatment of CHO cells recombinantly expressing the human A(2B) receptor with dithiothreitol led to a 74-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 55 publications
2
58
0
Order By: Relevance
“…In antagonist radioligand binding studies, BAY60-6583 showed high affinity for human (K i 212 nM) A 2B ARs. The nonselective A 2B agonist NECA displayed a 5-to 11-fold lower affinity than BAY60-6583 in binding studies versus the antagonist radioligand [ 3 H]PSB-603 (Schiedel et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In antagonist radioligand binding studies, BAY60-6583 showed high affinity for human (K i 212 nM) A 2B ARs. The nonselective A 2B agonist NECA displayed a 5-to 11-fold lower affinity than BAY60-6583 in binding studies versus the antagonist radioligand [ 3 H]PSB-603 (Schiedel et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…We have now experimentally supported the assumption that probably no disulfide bond is formed, by measuring ligand binding and receptor activation (by cAMP accumulation studies) without and after preincubation with the disulfide-reducing agent DTT. In contrast to many other GPCRs that require an intact extracellular disulfide bond for proper functioning [16,48,52], the rAdeR did not show any difference, neither in adenine binding, nor in adenine-induced adenylate cyclase inhibition (Fig. 10) after incubation with DTT to reduce accessible disulfide bonds.…”
Section: Discussionmentioning
confidence: 76%
“…AJ311952) used for the mutagenesis studies was cloned into the pUC19 vector and subcloned into the pFastBac1 vector (Invitrogen, Karlsruhe) after mutagenesis. Site-directed mutagenesis was performed as previously described [16]. In brief, complementary primers with the desired base exchanges were designed.…”
Section: Mutagenesis and Cloningmentioning
confidence: 99%
“…In the past when searching for a suitable expression system to characterize adenine receptors, we discovered that there is an endogenous high affinity binding site for adenine in CHO K1 cells [24]. We concluded that there may be an ortholog in the Chinese hamster genome as well, whose gene product might be responsible for [ 3 H]adenine binding in CHO K1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…* For both cell lines, the medium was supplemented with 10 % fetal calf serum, 100 U penicillin, and 100 μg/ml streptomycin. 1321N1 astrocytoma cells stably transfected with the mAde1R, and CHO K1 cells stably transfected with cAdeR were generated using a retroviral expression system as previously described [24]. In brief, GP + env AM12 packaging cells were transfected with retroviral vectors containing adenine receptor cDNA.…”
Section: Expression Of Adenine Receptors In Insect Cellsmentioning
confidence: 99%